IDENTIFICATION OF MONOD-IYERUSALIMSKII SYSTEM WITH LOOPBACK CONTROL - Pasichnyk, Roman M.; Pigovsky, Yuriy R. (International Journal of Computing, 2014)
Methods for structural and parametric identification of Monod-Iyerusalimskii system with loopback control are researched.